Reversal of fortune: a statistical analysis of penalty calls in the National Hockey League - Abrevaya, J.; McCulloch, R. (Journal of Quantitative Analysis in Sports, 2014)
This paper analyzes a unique data set consisting of all penalty calls in the National Hockey League between the 1995-1996 and 2001-2002 seasons. The primary finding is the prevalence of "reverse calls:" if previous penalties have been on one team, then the next penalty is more likely to be on the other. This pattern is consistent with a simple behavioral rationale based on the fundamental difficulty of refereeing a National Hockey League game. Statistical modeling reveals that the identity of the next team to be penalized also depends on a variety of other factors, including the score, the time in the game, the time since last penalty, which team is at home, and whether one or two referees are calling the game. There is also evidence of differences among referees in their tendency to reverse calls.